2022
DOI: 10.1097/ruq.0000000000000590
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effectiveness of Microvascular Doppler Ultrasound and Q-Pack in the Discrimination of Malign Thyroid Nodules From Benign

Abstract: In this prospective study, the diagnostic performance of MicroV Doppler ultrasonography (US) and Q-pack application in distinguishing malignant thyroid nodules from benign nodules will be examined. Given the emerging irregular vascular structures in malignant nodules, it is thought that MicroV Doppler US and Q-pack application can help in diagnosis. One hundred sixteen nodules that were suggested a biopsy by a clinician were examined with B-mode US, color, X-flow, and MicroV Doppler US, respectively. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…In studies performed according to vascular distribution patterns on Doppler US, hilar blood supply was observed in normal and reactive lymph nodes, while peripheral and mixed (hilar + peripheral) blood supply was seen in malignant lymph nodes ( 11 , 12 , 13 , 14 ) . However, the study by Ying et al .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In studies performed according to vascular distribution patterns on Doppler US, hilar blood supply was observed in normal and reactive lymph nodes, while peripheral and mixed (hilar + peripheral) blood supply was seen in malignant lymph nodes ( 11 , 12 , 13 , 14 ) . However, the study by Ying et al .…”
Section: Discussionmentioning
confidence: 96%
“…In studies performed according to vascular distribution patterns on Doppler US, hilar blood supply was observed in normal and reactive lymph nodes, while peripheral and mixed (hilar + peripheral) blood supply was seen in malignant lymph nodes (11)(12)(13)(14) . However, the study by Ying et al found that while peripheral blood supply was observed in metastatic lymph nodes, hilar vascular structures were also preserved in lymphomatous lymph nodes, and there was a tendency for both hilar and peripheral blood supply (15) .…”
Section: Discussionmentioning
confidence: 97%
“…For this reason, they also delete the slow flow which considered as an artifact. Doppler methods have been developed by different companies, which use the recently developed high frame rate and can see microvascular structures with its unique algorithm rather than large-medium diameter vascular structures (Esoate: Micro V Doppler and Toshiba: Superb microvascular imaging) (5,6). There are publications reporting that microvascular imaging techniques are extremely successful in superficial organs such as testis and breast in examinations performed with a lineer probe (13).…”
Section: Discussionmentioning
confidence: 99%
“…In grade 3 vascularity, more than two vascular structures are seen. Multiple irregularly shaped and curved microvascular structures in the center and periphery of the parenchyma is defined as grade 4 (5,6).…”
Section: Micro V Doppler Examinationmentioning
confidence: 99%